2014
DOI: 10.3136/fstr.20.337
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nickel and Silver Ions Using Eggshells with Membrane, Eggshell Membrane, and Eggshells

Abstract: IntroductionThe removal of toxic and heavy metals from wastewater is a matter of great interest in the field of water management. Recently, removal of heavy metal ions from industrial waste effluents has become more challenging due to the implementation of stricter laws and regulations to restrict the concentration of pollutants discharged into waters and soil to less than 1 mg/kg. Traditional methods of metal ion removal become inefficient at eliminating metal ions below this concentration. Therefore, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Relatively highest effectiveness of Ni removal by SW ( Figs. 3 and 4) may be justified by, as mentioned before, the largest use of under shell membranes with very good sorption characteristics [34]. The process of hydroxides generation during the process of the studied metal cations removal is confirmed by the solutions pH measurements results.…”
Section: Effectiveness Of Metals Removalsupporting
confidence: 67%
See 1 more Smart Citation
“…Relatively highest effectiveness of Ni removal by SW ( Figs. 3 and 4) may be justified by, as mentioned before, the largest use of under shell membranes with very good sorption characteristics [34]. The process of hydroxides generation during the process of the studied metal cations removal is confirmed by the solutions pH measurements results.…”
Section: Effectiveness Of Metals Removalsupporting
confidence: 67%
“…For the initial metal cations concentrations c Cu = 60 mg/dm 3 (0.94 mmol/dm 3 ), c Cd = 60 mg/dm 3 (0.53 mmol/dm 3 ) and c Pb = 150 mg/dm 3 (0.72 mmol/dm 3 ), the removal effectiveness decreased to approximately 85, 21 and 79 %, respectively [33]. Detailed studies on the effectiveness of Ni and Ag cations removal from solutions, with the use of eggshells divided by shells with organic membrane, shells without membranes and membranes alone, demonstrated that the removal effectiveness decreases along with the increase of the initial concentration of metal cations in the solution [34]. Moreover, it was demonstrated that removal effectiveness depends on the contact time, the relation V/m, where: V -a solution volume, m -shells mass, a solution temperature and pH.…”
Section: Effectiveness Of Metals Removalmentioning
confidence: 99%
“…Eggshells and their derivatives demonstrated a great potential for removing wastewater contaminated with nickel and silver ions. Comparing Eggshells and Eggshells with membrane, the values showed fast removal of Ni 2+ and Ag for Eggshell membrane [ 61 ]. Moreover, according to Park et al [ 62 ], the calcined eggshells showed a great potential for the adsorption of Cd 2+ and Cr while the natural eggshells enhanced the adsorption of Pb 2+ .…”
Section: Chemical and Physical Methodsmentioning
confidence: 99%
“…While some finds use in niche applications such as additive for animal feeds, most of it ends up in landfills resulting in environmental problems. , Eggshell waste is ranked 15th on the U.S. Environmental Protection Agency’s (EPA) list of food industry-caused pollution problems . Recently, to reduce the amount of eggshell waste going to landfills, its use as a filler in polymer matrix composites, as a chemical adsorbent in polluted water, and as a raw material for hydroxyapatite has been studied. Developing alternative ways to utilize eggshells could contribute to reducing the amount of waste disposed of in landfills. Consequently, it could contribute to reducing the cost of eggshell disposal and the environmental impact.…”
Section: Introductionmentioning
confidence: 99%